Perceived Effectiveness of Self Help Groups in Dairy Sector - Sajesh V K, (Indian Journal of Extension Education, 2015)
A study was conducted among members of SHGs in Chittoor district of Andhra Pradesh to assess the perceivedeffectiveness of SHGs in dairy sector in terms of resource, technology, extension, marketing and capacity development.Considerable improvement was observed in all the aspects studied, indicating that group mobilization have potential toovercome the multiple constraints faced by small farmers at individual level. Major factors affecting the effectiveness ofdairy SHGs were found to be functional linkage, support from promoting institution and amount of credit availed.